Osteosarcoma exocytosis of soluble LGALS3BP mediates macrophages toward a tumoricidal phenotype. (1st March 2022) - Li, Jing; Zhao, Chenguang; Li, Yuhuan; Wen, Junxiang; Wang, Shuang; Wang, Difan; Dong, Hui; Wang, Dong; Zhao, Yonglin; Wang, Xiaohui; He, Xijing; Qin, Jie
Abstract: This study aimed to elucidate the interactions between osteosarcoma (OS) and M1 macrophages infiltrated into the tumor microenvironment and to explore the underlying mechanisms whereby M1 macrophages influence the growth of OS, so that novel treatments of OS can be developed. A transwell co-culture system, an indirect conditioned medium culture system and two orthotopic bearing OS models were established to assess for the interplay between M1 macrophages and OS. We found that the co-culture of M1 macrophages with OS cells significantly inhibited the growth of the tumor cells by inducing apoptosis. Furthermore, HSPA1L secreted by M1 macrophages exerted this anti-tumor effect through the IRAK1 and IRAK4 pathways. LGALS3BP secreted by OS cells bound to the ligand LGALS3 on M1 macrophages and thereby induced the secretion of Hspa11 via Akt phosphorylation. In vivo experiments demonstrated that the culture supernatant of OS-stimulated M1 macrophages significantly inhibited the growth of OS, whereas silencing Lgals3bp promoted the progression of OS. In conclusion, OS modifies the phenotype of tumor-associated macrophages (TAMs) and thereby influences the apoptosis of OS cells through soluble factors. The modulation of TAMs may be a promising and effective therapeutic approach in OS. Highlights: Symbiotic macrophage-osteosarcoma cell interactions alter M1 macrophages toward a tumoricidal phenotype. Soluble Lgals3bp secreted by osteosarcoma binds its ligand lgals3 on M1 macrophages stimulates the secretion of Hspa1l. Extracellular Hspa1l promotes the apoptosis of OS cells via IRAK1 and IRAK4. High expression levels of LGALS3BP were associated with good prognosis in mouse OS model and patients with sarcoma.